Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration Nutrition, and the Report on “Criticism and Improvement of Diets,” published by the Ministry of Health). Others aim at the optimum diet — the diet which will enable us to maintain an ideal standard of nutrition, defined by Sir John Orr as “a state of well-being such that no improvement can be effected by a change in the diet.” Class Distinction in Health? We believe that we should be concerned not with the minimum diet but with the best (optimum); or to put it another way, the only diet which we can regard as satisfactory, in the light of existing knowledge of nutrition, is one that will enable every member of the community to attain a standard of health and growth equal to that enjoyed by the healthiest sections of the community. To aim at a lower general standard is to admit the necessity of class distinction in health. Can We Raise Health Level Above “Minimum”? Certain nutrition experiments in recent years have shown the possibility of raising the level of nutrition beyond the standard attainable on a minimum diet. The large-scale experiment in 1930 among Lanarkshire school children to test the value of milk, produced striking results. 20,000 children were under review, 10,000 receiving a ration of ¾ pint of milk per day, the others receiving no ration. At the end of four months, the children receiving milk showed a greater rate of growth and a marked improvement in health. The preface to the report says: “The results ... demonstrate that the addition of milk to the diet of children has a striking effect in improving physique, and general health, and increasing mental alertness. They suggest also that, apart from its own food value, milk enables the other constituents of the ordinary diet to be fully utilised as growth factors.” Both groups of children were mixed — well nourished as well as poorly nourished children being included. But the marked improvement in the milk-ration children was not confined to those who had been ill-nourished. 9 127/NU/5/5/1/12